Long‐term changes to plankton communities in artificially heated lakes - Kingsly C. Beng; Slawek Cerbin; Michael T. Monaghan; Justyna Wolinska (Limnology and Oceanography, 2025)
Increased surface‐water temperatures and nutrient enrichment are predicted to alter planktonic communities, impacting biodiversity and ecosystem functioning. While short‐term mesocosm studies have reported temperature‐ and nutrient‐driven effects, long‐term observations from natural systems remain limited. We studied seasonal plankton communities in 10 lakes in central Poland, five warmed by power plant discharge for six decades and ~ 2°C warmer (annual mean) than control lakes. Based on environmental DNA (eDNA) relative read abundance, green algae (Chlorophyta) were up to 15% more abundant in heated lakes, while golden algae (Chrysophyceae) were up to 7% more abundant in control lakes. Heated lakes exhibited higher diversity of diatoms, green algae, golden algae, cercozoans, basidiomycetes, and chytrids, especially in summer. Their plankton assemblages were compositionally distinct and showed reduced seasonal variability. Multiple regression revealed that rising temperature, interacting with elevated nutrients, reduced diversity in many plankton groups. Warming favored heat‐adapted taxa, driving compositional shifts. By providing insights into the long‐term impacts of anthropogenic warming, this study underscores the importance of integrating temperature‐nutrient interactions in predicting ecosystem responses to climate change.